Analysis the Effectiveness Management of Community Learning Center Bina Kreasi Bangsa in East Jakarta - Mufidah, Firda; Matin, Matin; Susanto, Teguh Trianung Djoko (International Education Trend Issues, 2024)
The purpose of this research was to deeply understand the effectiveness management of Community Learning Center Bina Kreasi Bangsa. The effectiveness of management is assessed or measured through its core functions: planning, organizing, implementing, controlling, and evaluating. The research method was descriptive qualitative. Data collection techniques used interviews, observations, and documentation studies. The result of this research show the the effectiveness of management in Bina Kreasi Bangsa has been effective from the analysis of planning, organizing, implementing, controlling, and evaluating because of management. Bina Kreasi Bangsa has met the criteria or standard indicators of the effectiveness of an institution.